Soberania alimentar e o assentamento Mulungu no semiárido cearense - Pereira, Simone Silva [UNESP] (2014)
The starting point of this study is the need for change in the agrarian structure of the country. Land concentration has led many people to suffering and misery, thus causing tensions and conflicts. The objective of this paper is to present the strategies of building food sovereignty from the conception of organized peasants, having as territory of research the Mulungú Settlement, located in the state of Ceará, observing the way they guarantee the production, access and consumption of food. Our field of study goes beyond the settlement and the peasants to also address the relationship of peasants organized with society, because this agrifood management is wrapped in a dimension that is crucial and determines the culture and identity of the people. We also approached what La Via Campesina International is thinking regarding the internationalization of the struggle of the peasants in a non-hegemonic perspective. The theoretical study, field research and the systematization of research point to the need of a globalization food sovereignty policy, which means the implementation of public policies that value local production of healthy and sufficient food for good nutrition of the population, and an agricultural sector that contributes to the generation of employment, housing, land, water and clean and free air for everyone. In these frameworks, the research examines a case of attempt to build policies for food sovereignty, from the organization of workers in the semiarid region of Ceará and the forms, limits and challenges to the peasant organizations with regard to the organization of labor for healthy food production in adverse conditions and against agribusiness